2006
DOI: 10.1002/macp.200600109
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Metallocenic sPP with Time: Changes in Crystalline Content and Enthalpic Relaxation

Abstract: Summary: The structural evolution of a metallocenic syndiotactic poly(propylene), sPP, with time has been studied. Due to the low syndiotactic content, the analyzed sPP sample can be easily quenched to a completely amorphous state. This amorphous sample, when left at room temperature is able to crystallize at relatively long times. The degree of crystallinity, as a function of time, has been analyzed by X‐ray diffraction and DSC. The DSC melting curves show the presence of a very important low‐temperature endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…This multiple melting behavior in polymers has been explained by assuming successive melting-recrystallization processes [2326], existence of dual lamellar populations [27,28] or presence of two or more polymorphs [2932]. The former assumption seems to be the cause for this thermal response in the specimens under study, since a unique PCL crystalline structure is developed, as deduced from WAXS measurements and two crystallite populations have not been apparently observed, as revealed in the SAXS profiles within the temperature range of interest.…”
Section: Resultsmentioning
confidence: 99%
“…This multiple melting behavior in polymers has been explained by assuming successive melting-recrystallization processes [2326], existence of dual lamellar populations [27,28] or presence of two or more polymorphs [2932]. The former assumption seems to be the cause for this thermal response in the specimens under study, since a unique PCL crystalline structure is developed, as deduced from WAXS measurements and two crystallite populations have not been apparently observed, as revealed in the SAXS profiles within the temperature range of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of tan δ for the present sPP sample (0.15) corresponds to a semicrystalline polymer (tan δ amorphous phase > 1.2) . The γ relaxation is observed in Figure at around −80 °C attributed to local motions of methyl groups directly connected to the main backbone in sPP and its copolymers . This relaxation is quite less broad than that with similar molecular origin found in iPP.…”
Section: Resultsmentioning
confidence: 51%
“…The β relaxation is identified with the glass transition of sPP, related to generalized motions in the amorphous region, with intensity and location depending on the presence of crystalline phase. The intensity of tan δ for the present sPP sample (0.15) corresponds to a semicrystalline polymer (tan δ amorphous phase > 1.2) . The γ relaxation is observed in Figure at around −80 °C attributed to local motions of methyl groups directly connected to the main backbone in sPP and its copolymers .…”
Section: Resultsmentioning
confidence: 65%
“…Analyzing the results of DMTA, it can be observed that at temperatures higher than T g , the values of storage modulus are very low and practically the same for all eco‐composites, but with increasing temperature and reaching the region of the cold crystallization, the moduli are increasing again. Although this behavior is not usual, it has been previously observed in metallocenic syndiotactic polypropylene, as a result of cold crystallization 29…”
Section: Resultsmentioning
confidence: 62%